2011
DOI: 10.3109/13625187.2011.589920
|View full text |Cite
|
Sign up to set email alerts
|

Unwanted pregnancy among Chinese renal transplant recipients

Abstract: Of the 647 eligible patients, 98 (15%) reported 133 unwanted pregnancies post-transplantation. In this group (n = 98), despite an awareness of the available contraceptive measures, 56% had not applied any method of contraception, while 20% had relied on the rhythm method, and in only 12% of the cases male condoms had been used. The most common reason for not using contraception was a failure to realise that their reproductive function had been restored to normal soon after transplantation (19%). CONCLUSION In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…While 15% of the cohort had an unwanted pregnancy, no pregnancies occurred in the IUD group. 12 Similar results were reported in KT and LT recipients using hormonal IUDs, with no pregnancies in 3 years of follow-up. 8,13,14 Current data also indicate that immunosuppressed women have no increased risk of pelvic inflammatory disease compared to the general population of non-IUD users.…”
Section: Concerns Surrounding the Use Of Iuds In Transplant Recipientssupporting
confidence: 75%
See 2 more Smart Citations
“…While 15% of the cohort had an unwanted pregnancy, no pregnancies occurred in the IUD group. 12 Similar results were reported in KT and LT recipients using hormonal IUDs, with no pregnancies in 3 years of follow-up. 8,13,14 Current data also indicate that immunosuppressed women have no increased risk of pelvic inflammatory disease compared to the general population of non-IUD users.…”
Section: Concerns Surrounding the Use Of Iuds In Transplant Recipientssupporting
confidence: 75%
“…15,16 There have been no published cases of pelvic inflammatory disease among >200 KT and LT recipients to date. 8,10,12,13 …”
Section: | Contraception In Transplant Recipientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Chinese questionnaire-based study reported no pregnancies in 178 RT recipients with IUDs, although other complications were not discussed. (4) Two case series of 29 transplant recipients (3 LT recipients) with levonorgestrel IUDs reported no pregnancies or pelvic infections (median follow-up, 44 months; range, 1-111 months), although half of the women in 1 study used additional barrier protection after IUD placement. (5,6) In 2016, the Centers of Disease Control and Prevention (CDC) published an updated version of the US Medical Eligibility Criteria for Contraceptive Use (USMEC), providing recommendations (Table 1) on the safety of contraceptive methods in solid organ transplantation.…”
Section: To the Editormentioning
confidence: 99%
“…The treating physician and the transplant nurse are the most suitable to provide initial counseling and to reinforce this advice in the outpatient setting. 25 …”
Section: Introductionmentioning
confidence: 99%